Using retrospective analysis of race results to determine success in elite cycling - Hopker, L.; Dietz, K. C.; Schumacher, Y. O.; Passfield, L. (Journal of Science and Cycling, 2015)
Background: Achieving success in elite athletic performance is a major research focus for sports scientists. It is now generally accepted that athletes have to undertake many years of training to reach the top levels of endurance sports. However, debate is evident within the literature as to whether athletes have to participate in elite junior competitions to achieve top results as an adult (senior) (Schumacher & Muller, 2001: Journal of Sports Medicine and Physical Fitness, 41, 139-46; Schumacher et al., 2006: Journal of Sports Sciences, 24, 1149-56). Moreover, there has been historical debate as to whether "success breeds success" in sporting competitions (cf Bar-Eli et al., 2006, Psychology of Sport and Exercise, 7, 525-53); i.e. if athletes win once, are they then more likely to realize further success during their careers?